Differentiation of ruminal bacterial species by enzyme-linked immunosorbent assay using egg yolk antibodies from immunized chicken hens. - Ricke, S C (1988)
Cross-reactivity among four species of ruminal bacteria was examined by using egg yolk antibodies from immunized Leghorn laying hens and an enzyme-linked-immunosorbent assay. The effects of the four species on the hens were compared on various days postimmunization. Hens injected with the same bacterial species had similar apparent antibody levels over the entire postimmunization period, but only Bacteroides ruminicola B1(4) and Selenomonas ruminantium D antigens elicited early increases in apparent antibody levels during weeks 2 and 3. Antibody cross-reactivity was greatly reduced by week 2, except for antibodies against Streptococcus bovis JB1.